(untitled) (Research, Society and Development, 2020)
The present article constitutes as a review of the study “A foreigner in family: be deaf as an linguistic difference” and aims to reflect about the results of a doctoral thesis with the study developed at a private university. Through a qualitative research, with ethnographic design, which took place from May 2010 to May 2012, with ten deaf university students. These students, seven male and three female, between 18 and 38 years old, who used sign language as the main means of communication on Campus, coming from plenty of courses, besides the participation of their family, in the investigation. The Focal Group and semi-open interview were used, composed of two groups, one with deaf people and the other with their hearing family. As a resource for data analysis, the Nvivo software was used, pointing out eight categories: Communication, Compulsory Oralization, Deaf Culture, Prejudice, Inappropriate Schooling, Family, Perspective of the Difference and Medical Perspective, which reveal correlations between themselves and demonstrate divergences of perceptions, between both groups. Making it clear that the deaf people support the perspective of being deaf as a difference, while their family members point it as a disability, from the medical model perspective. The study review found that deaf people do not accept the perspective of disability, as their hearing family, as the society, ensure that there is a missing and that the condition of being deaf is a disability.